When Retinal Vasculitis Wears a Mask: Unveiling Retinal Vasculitis Presented as Branch Retinal Vein Occlusion in a Young Male Patient: Poster Presentation - Case Report - Resident - Lia Amanda; Andi Marsa Nadhira; Yulia Aziza; Rina La Distia Nora (Majalah Oftalmologi Indonesia, 2023)
Introduction : Retinal vasculitis can present with a range of clinical features. Correct diagnosis and prompt treatment are essential to prevent permanent visual loss. We describe a case of retinal vasculitis with branch retinal vein occlusion (BRVO) as initial diagnosis, which is a rare manifestation in a young individual without any vascular risk factors. Case Illustration : A 24-year-old male was referred to our center with a sudden onset of blurry vision of his left eye. He was previously diagnosed with BRVO. The patient denied having any chronic diseases, fever, or sore throat. Visual acuity was 6/18 on the left eye and 6/6 on the right eye, respectively. The anterior segment showed no abnormalities. However, fundus examination revealed prominent retinal sheathing, retinal whitening at the inferior quadrant, and macular star. Systemic diseases, such as Bechet disease, sarcoidosis, and systemic lupus erythematosus were excluded by ancillary tests. One month after the initial examination, the patient reported worsening of vision. Funduscopic examination revealed preretinal hemorrhages and macular star. The patient then received intravitreal injection of anti-vascular endothelial growth factor (VEGF), which helped to resolve the hemorrhage and improve vision. Discussion : Further investigations, such as fundus fluorescein angiogram, may aid in the diagnosis and management of this condition. Anti-VEGF therapy may be a useful treatment option for retinal vasculitis-associated hemorrhages. Conclusion : Our case highlights the importance of considering retinal vasculitis as a differential diagnosis in young patients presenting with BRVO, even in the absence of traditional risk factors.